Infrastructural frontiers: Terrains of resistance at the material edge of the state. Issue 136 (November 2022) - Schouten, Peer; Bachmann, Jan
Abstract: This introduction to the special issue lays out some of the theoretical underpinnings of the notion of the 'infrastructural frontier'. We begin by considering infrastructures as material geographies of power, before moving on to highlight how broader processes of order-making and resistance often become operational at the material edges of states: the places where transport and communication networks peter out and give way to terrains less amenable to remote control. Weaving together insights from the contributions to this special issue, we then show how the concept of the infrastructural frontier productively intervenes in the wider discussion on material geographies, frontiers, and borderlands, by placing the interplay between unsettled infrastructures and unsettled configurations of power at the edge of the state at the center of interest.